ENVIRONMENTAL LITERACY IN MIDDLE SCHOOL: ECOLOGICAL KNOWLEDGE, COGNITIVE SKILLS, ENVIRONMENTAL AFFECT, AND PRO-ENVIRONMENTAL BEHAVIOR - Napitupulu, Nurasyah Dewi; Novianti, Iin; Iduard, Iduard; Rutmiyanti, Rutmiyanti; Ibrahim, Ibrahim; Embatau, Katarina Selmi (Universitas Labuhanbatu, 2025)
Purpose-The research examines the environmental literacy of the VIII grade students of SMP Negeri 1 Banawa based on four principal indicators: ecological knowledge, cognitive skills, environmental affect, and pro-environmental behavior. The research aims to assess the interrelations among these indicators and to provide recommendations for enhancing environmental literacy in schools with comparable settings.Methodology-The method of study is descriptive quantitative, which describes and analyzes systematically based on the students' environmental literacy indicator measurement results. The sample was 32 students of VIII grade, who were selected by using a total sampling technique. The instrument was a questionnaire containing multiple-choice tests measuring ecological knowledge and cognitive ability and a Likert scale measuring students' environmental affects and pro-environmental behavior. The MSELS model informed the structure of each of the sections of the questionnaire. The questionnaire data were analyzed using descriptive statistics to compute percentages and the means of each indicator and simple regression analysis to compute relationships among variables.Findings-The research results show that the overall environmental literacy students were classified as good, with a mean score of 76.64%. In particular, ecological knowledge was 77.09%, cognitive skills 67.19%, environmental affect 81.45%, and pro-environmental behavior 80.82%. The results of the regression analysis indicated that environmental affects have a significant impact on pro-environmental behavior.Significance- Environmental affects are important in encouraging students' pro-environmental behavior and account for 54.2% of the variation in pro-environmental behavior. The findings highlight that pro-environmental behavior is better brought about by developing students' emotional engagement and worry about the environment rather than through the single-minded development of ecological knowledge. Keywords : Environmental Literacy, Ecological Knowledge, Cognitive Skills, Environmental Affect, Pro-environmental Behavior